2018
DOI: 10.1002/pd.5274
|View full text |Cite
|
Sign up to set email alerts
|

Fetal sex determination in twin pregnancies using cell free fetal DNA analysis

Abstract: While non-invasive prenatal testing is a screening method and confirmatory results must be obtained by ultrasound or genetic diagnosis, the sex-score determination presented herein offers an accurate and useful approach to characterizing fetus sex in twin pregnancies in a non-invasive manner early on in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Recently, Milan and colleagues investigated the accuracy of a sex prediction model based on the normalized chromosome value (NCV) of the sex chromosomes by linear regression. 20 Without discriminating between mono- or dichorionic pregnancies, the authors reported a detection rate of 98% for fetuses sex classification with a sensitivity and specificity of 97% and 95%, respectively. Here, we show that a two-step linear regression with incorporation of fetal fraction in the model increases the performance for sex determination.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Milan and colleagues investigated the accuracy of a sex prediction model based on the normalized chromosome value (NCV) of the sex chromosomes by linear regression. 20 Without discriminating between mono- or dichorionic pregnancies, the authors reported a detection rate of 98% for fetuses sex classification with a sensitivity and specificity of 97% and 95%, respectively. Here, we show that a two-step linear regression with incorporation of fetal fraction in the model increases the performance for sex determination.…”
Section: Discussionmentioning
confidence: 98%
“…One discordance (misclassified male‐female twins as female‐female twins) might be due to some complex biological reasons such as an unbalanced translocation between the X and Y chromosome or fetal sex chromosome mosaicism, given the fetal fraction was as high as 15.55% and no abnormal information was observed in the test. A recently published study used a sex score method, which was determined by normalized chromosome values for chromosomes X and Y for fetal sex prediction with 98% accuracy (95% CI, 90%‐99%) in twin pregnancies. Here, we also provided an assessment for sex determination in twin and triplet pregnancies; however, the sex predictive performance needs to be further tested.…”
Section: Discussionmentioning
confidence: 99%
“…1 a). Since FF can be estimated based on amount of Chr Y [ 6 ], we compared FF estimations by two different methodologies: the SeqFF approach [ 7 ], and another method based on Chr Y [ 6 ]. In the first blood sample, SeqFF estimated overall FF of 6.4%, whereas the Y chromosome-based method yielded 73.7%.…”
Section: Case Presentationmentioning
confidence: 99%